2013
DOI: 10.1056/nejmc1307177
|View full text |Cite
|
Sign up to set email alerts
|

Surgery versus Physical Therapy for Meniscal Tear and Osteoarthritis

Abstract: Matava, Matthew J.; Smith, Matthew V.; Wright, Rick W.; and et al, ,"Surgery versus physical therapy for a meniscal tear and osteoarthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Several randomized controlled trials designed to evaluate the effect of arthroscopy on middle-aged patients with knee pain with or without OA have, however, not shown any beneficial effect of surgery over placebo surgery or physiotherapy. (Moseley et al 2002, Herrlin et al 2007, Kirkley et al 2008, Katz and Losina 2013, Sihvonen et al 2013, Yim et al 2013). Only 1 study has indicated a slightly better effect of knee arthroscopy with partial meniscectomy than of physiotherapy alone, but this study did not include any sham operation (so a stronger placebo effect in surgery patients cannot be excluded) (Gauffin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials designed to evaluate the effect of arthroscopy on middle-aged patients with knee pain with or without OA have, however, not shown any beneficial effect of surgery over placebo surgery or physiotherapy. (Moseley et al 2002, Herrlin et al 2007, Kirkley et al 2008, Katz and Losina 2013, Sihvonen et al 2013, Yim et al 2013). Only 1 study has indicated a slightly better effect of knee arthroscopy with partial meniscectomy than of physiotherapy alone, but this study did not include any sham operation (so a stronger placebo effect in surgery patients cannot be excluded) (Gauffin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A multi-centred RCT by Katz et al published in the New England Journal of Medicine also compared APM with physical therapy [ 19 ]. Subjects were symptomatic patients aged 45 years and over with a meniscus tear and evidence of OA (0-3 by Kellgren-Lawrence criteria).…”
Section: Introductionmentioning
confidence: 99%
“…According to the evidence-based guideline of American Academy of Orthopaedic Surgeons (AAOS), treatment for OA including glucosamine, chondroitin, acupuncture, physical agents, and lateral wedge insoles were not recommended while the only pharmacologic treatment recommended for OA was nonsteroidal anti-inflammatory drugs (NSAIDs; oral or topical) or tramadol for patients with symptomatic OA of the knee, merely providing symptomatic relief from pain and failing to prevent cartilage damage and subsequent destruction of other joint tissues [ 1 ]. In recent years, New England Journal of Medicine published a series of results of controlled clinical trials demonstrating little effect of arthroscopic surgery for the treatment of OA [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%